PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH PADA KABUPATEN/KOTA DI INDONESIA - Annisa, Andi Nur; Abdullah, Muhammad Ikbal; Iqbal, Muhammad; Yamin, Nina Yusnita (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2020)
This study aims to determine and analyze simultaneously and partially the influence of local government characteristics on the financial performance of local governments by using a proxy of the characteristics of local governments, namely the size of the regional government, balance funds, and regional spending. The population in this study is the regencies/cities in Indonesia in 2016 as many as 504. The sampling technique used purposive sampling and obtained a sample of 207. The data analysis technique used multiple regression analysis. Based on the results of the study found that simultaneously the characteristics of local governments affect the financial performance of local governments. The size of the regional government, balance funds, and regional expenditure have a partial effect on the financial performance of local governments.